Physical and electrical parameters measurement module in solar panel physics laboratory Politeknik Negeri Bali - Aryasa Wiryawan, I Made; Sugiarta, I Nyoman; Teresna, I Wayan (Proceedings, 2018)
Practice related to Solar Panel for Electrical Engineering program students conducted in Physics Laboratory of Electrical Engineering Department of Politeknik Negeri Bali as the introduction of solar cell still use equipment separately so that the measurement result not yet optimal. Based on these conditions, this study aims to create a Solar Panel practice module as a student practice tool and increase student competence in performing measurements of Solar Cell output in Physics Laboratory. Methods in the manufacture of modules include: determining the types of measuring devices and solar cell specifications, drawing solar cell module designs and determining the position of solar cells with a slope of 0 0 , 30 0 , 60 0 and 90 0 . Measurements include Open Circuit Voltage (Voc) and Short Circuit Current (Isc) from series of two solar panels in series and parallel. Based on the measurements made in the Solar Panel conditions the series circuit obtained Voc value changed 0 - 7 volts, Isc ranged from 1 to 6 Ampere, whereas in parallel series Voc measurement results change between 0 - 1 Volt and Isc value changes between 2- 11 Ampere. The output of physical parameters (angle) of influence is not significant because the slope angle of the Solar Panel is facing east (sunrise). The effect of Solar Panel Output Isc is a bright or sunny cloudy weather with a temperature level  between 22 0 C – 42 0 C.